Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/sms.13608
|View full text |Cite
|
Sign up to set email alerts
|

Training intensity‐dependent increases in corticospinal but not intracortical excitability after acute strength training

Abstract: The purpose of this study was to determine whether the increases in corticospinal excitability (CSE) observed after one session of unilateral isometric strength training (ST) are related to changes in intracortical excitability measured by magnetic brain stimulation (TMS) in the trained and the contralateral untrained biceps brachii (BB) and whether such changes scale with training intensity. On three separate days, 15 healthy young men performed one ST session of 12 sets of eight isometric contractions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…To date, it remains unclear how rapidly these neural responses to strength training occur following the commencement of a strength training program. Transcranial magnetic stimulation (TMS) studies have emerged in recent years to study the effects of strength training on the synaptic activity of the cortico-cortical circuitry of the primary motor cortex and of the corticospinal tract (CST) following a bout of strength training [2][3][4][5][6][7][8][9][10]. Leung et al [6] reported that a single session of heavy-load strength training (75%1RM) of the biceps brachii increased the amplitude of motor-evoked potentials (MEPs) induced by single-pulse TMS, a finding consistent with Latella et al [5] who also showed increased MEP amplitude following both heavy-load and hypertrophy-based strength training (<75% 1RM).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…To date, it remains unclear how rapidly these neural responses to strength training occur following the commencement of a strength training program. Transcranial magnetic stimulation (TMS) studies have emerged in recent years to study the effects of strength training on the synaptic activity of the cortico-cortical circuitry of the primary motor cortex and of the corticospinal tract (CST) following a bout of strength training [2][3][4][5][6][7][8][9][10]. Leung et al [6] reported that a single session of heavy-load strength training (75%1RM) of the biceps brachii increased the amplitude of motor-evoked potentials (MEPs) induced by single-pulse TMS, a finding consistent with Latella et al [5] who also showed increased MEP amplitude following both heavy-load and hypertrophy-based strength training (<75% 1RM).…”
Section: Introductionmentioning
confidence: 99%
“…Leung et al [6] reported that a single session of heavy-load strength training (75%1RM) of the biceps brachii increased the amplitude of motor-evoked potentials (MEPs) induced by single-pulse TMS, a finding consistent with Latella et al [5] who also showed increased MEP amplitude following both heavy-load and hypertrophy-based strength training (<75% 1RM). Recently, Mason et al [7] and Colomer-Poveda et al [2] reported that an acute bout of heavy-load strength training of the biceps brachii increased CSE, but interestingly, both of these studies included a light-load ST group. However, the findings of Mason et al [7] were in contrast to Colomer-Poveda et al [2], whereby light-light strength training increased CSE in the former study, but remained unchanged in the latter study.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations